2021
DOI: 10.1007/s12571-021-01142-2
|View full text |Cite|
|
Sign up to set email alerts
|

Mapping the production-consumption gap of an urban food system: an empirical case study of food security and resilience

Abstract: Urban food systems are complex and increasingly recognised as not being sustainable, equitable or resilient. Though globalisation and lengthening of agrifood supply chains has brought many benefits, such as year-long availability of fresh produce and modernisation opportunities for some developing regions, they have increased reliance on food imports and reduced the food and nutrition resilience of many cities. This premise has been widely witnessed following recent financial, climatic and pandemic driven disr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…In European countries, adolescents indicated the influence of large food manufacturers and advertisers as important drivers of the consumption of unhealthy food [ 22 ]. Others have reported a high preponderance of fast-food establishments stimulating easy purchasing of unhealthy food [ 22 , 23 , 24 ], and thus consumption of high-calorie and low-nutrient food [ 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In European countries, adolescents indicated the influence of large food manufacturers and advertisers as important drivers of the consumption of unhealthy food [ 22 ]. Others have reported a high preponderance of fast-food establishments stimulating easy purchasing of unhealthy food [ 22 , 23 , 24 ], and thus consumption of high-calorie and low-nutrient food [ 25 , 26 , 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the reviewed tools mostly address the environmental dimension of sustainability (86%). Moreover, even though social issues are the main concern of local governments when developing urban agriculture initiatives [32], this is less reflected in the support offered by the tools reviewed (74% vs. 86% on environmental issues). Likewise, although urban food production can improve the economic sustainability of a city [33], the economic dimension is least represented among the studied tools (66%).…”
Section: Characterisation Of Toolsmentioning
confidence: 99%
“…Due to challenges after production, research has revealed untapped entrepreneurial opportunities in the food value chain distribution sector (Anastasiadis and Poole, 2015). According to research, the value chain is severely disrupted due to the poor relationship between farmers and market players, insufficient infrastructure, and inadequate governance systems (Jensen and Orfila, 2021). Furthermore, governments' restricted political and economic relationships harm the supply chain's efficiency and responsiveness (Halabi and Lin, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%